The Hematopoietic Stem Cell Transplant Comorbidity Index (HCT-CI) Can Predict for 30-Day Readmission Following Autologous Stem Cell Transplant for Lymphoma and Multiple Myeloma - Jaglowski, Samantha M. (2014)
Patients who undergo autologous stem cell transplant (ASCT) for hematologic malignancies frequently have multiple comorbidities. The hematopoietic cell transplantation-specific comorbidity index (HCT-CI), a transplant-specific modification of the Charlson Comorbidity Index, can predict risk of readmission following allogeneic stem cell transplant. Its utility in the autologous setting is unknown. We evaluated 620 patients who underwent ASCT at the Ohio State University from 2007 to 2012 for lymphoma or multiple myeloma (MM) to identify factors associated with readmission. Univariable and multivariable logistic regression were used to estimate the odds of readmission within 30 days of discharge following ASCT. A Cox proportional hazards model was used to evaluate overall survival (OS). Sixty-four patients were readmitted within 30 days; the most common indications were fever and prolonged gastrointestinal toxicity. Multiple myeloma compared with lymphoma (OR 1.89, 95% CI 1.06–3.38, p=0.03), HCT-CI≥3 (OR 1.74, 95% CI 1.03–2.96, p=0.04), and length of hospitalization ≥28 days (OR 3.14, 95% CI 1.26–7.83, p=0.01) remained significantly associated with 30-day readmission in a multivariable model. While the model had excellent fit (p > 0.75), its ability to predict individual patients who would be readmitted was less than acceptable (ROC=0.64, 95% CI: 0.57–0.71). In a multivariable proportional hazards model, 30-day readmission (HR 1.81, 95% CI 1.04–3.18, p=0.04), length of hospitalization ≥28 days (HR 4.93, 95% CI 2.65–9.18, p<0.001), and chemorefractory disease (HR 3.08, 95% CI 1.74–5.43, p<0.001) were independently associated with inferior OS, but HCT-CI was not. Evaluation of other assessment tools may allow for better prediction of outcomes following ASCT.